Crisis Management in Security Environment - Mikolaj, Jan (Communications - Scientific letters of the University of Zilina, 2005)
Public security is, in present-days, the key element of society in national and in international space. The jeopardy of the society obtained unprecedented measure especially after terrorists’ threat and attacks. The defence of the society over these threats is ethical and overall human problem. A human being is jeopardized by the ideological or by quasi-humane thoughts and enforced by their power, but also the nature hard acts against him. The interest of governments is to secure the society against the nature disfavour and to secure it also against jeopardised antihuman powers. Risk in human-doing, crisis in technical, technological, economic and social matters are sources of inequality in society. This article is an essay of security research and its aim is to point out to discrepancies in human doing and human being mainly from the viewpoint of crises influence of human and society security.